Recovering the Damping Rates of Cyclotron Damped Plasma Waves from Simulation Data (Communications in Computational Physics, 2018)
Plasma waves with frequencies close to the particular gyrofrequencies ofthe charged particles in the plasma lose energy due to cyclotron damping. We brieflydiscuss the gyro-resonance of low frequency plasma waves and ions particularly withregard to particle-in-cell (PiC) simulations. A setup is outlined which uses artificiallyexcited waves in the damped regime of the wave mode's dispersion relation to trackthe damping of the wave's electromagnetic fields. Extracting the damping rate directlyfrom the field data in real or Fourier space is an intricate and non-trivial task. We thereforepresent a simple method of obtaining the damping rate Γ from the simulationdata. This method is described in detail, focusing on a step-by-step explanation of thecourse of actions. In a first application to a test simulation we find that the dampingrates obtained from this simulation generally are in good agreement with theoreticalpredictions. We then compare the results of one-, two- and three-dimensional simulationsetups and simulations with different physical parameter sets.